Pengaruh Baby Spa(Solus Per Aqua) Terhadap Pertumbuhan Bayi Usia 3-4 Bulan - Setiawan, Deny, Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes, Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Spa (solus per aqua) on the body of the baby and children aged 3-4 months can be done in two ways, namely bathing or swimming and massage. Soaking and swimming will stimulate the baby's motor movements, with water playing the muscles baby will develop well, the joints will grow optimally, increased body growth, and the body becomes supple. Infants massage is beneficial to promote weight loss, growth, endurance, concentration babies, making sleep more soundly, and nurture the bond of affection between the masseuse and the baby.To determine the effect on growth of baby spa infants aged 3-4 months.There is a baby spa influence on the growth of infants aged 3-4 months; there is a massage influence on the growth of infants aged 3-4 months; there is a difference between on the effects of baby spa with massage on the growth of infants aged 3-4 months.By doing baby spa regularly can increase weight infants aged 3-4 months.